Histopathologic Evaluation of Follicular Tissues Associated with Impacted Third Molars - M. Khorasani; F. Samiezadeh (Tehran University of Medical Sciences, 2008)
Objective: The aim of the present study was to histopathologically evaluate follicular tissues of third molars with pericoronal radiolucenciesof less than 2 millimeters. Materials and Methods: In this descriptive analytic study, 100 impacted third molars with normal follicular spaces were removed and their pericoronaltissues submitted for histopathologic examination. Different characteristicsof the epithelium and connective tissue were evaluated in all cases. Statisti-cal analysis was performed using chi square and Mann-Whitney tests. Results: In our study sample, 74% of the patients were female and 26% were male, ranging in age from 13 to 54 years (mean, 25.3 years). Lining epithelium was observed in 69% of the specimens of which 31%, 23% and 14% was cuboidal, squamous and columnar, respectively. A significant re-lationship was found between the presence of squamous epithelium and pa-tient age (P<0.05). Nonspecific chronic inflammation was the only patho-logic finding observed in 44% of the specimens. Inflammation was signifi-cantly associated with age and squamous metaplasia (P<0.05). Conclusion: Considering that pathologic lesions were not observed in anyof the studied cases, unerupted third molars should not be removed unless there is a clinical indication to do so, or in case the impacted molar shows evidence of pathological changes. Follow-up is suggested for asympto-matic impacted third molars.